Islam in Indonesian Foreign Policy: Assesing Impacts of Islamic Revivalism during the Soeharto Era - Azra, Azyumardi (Studia Islamika, 2000)
In the last two decades, the Islamic world has witnessed something of an Islamic revival. Indonesian Muslims to a certain extent are likewise affected by the euphoria of Islamic revivalism; and there is much evidence to suggest that Islam, like other religions in Indonesia, is also experiencing a revival. As a result frequently since the end of the 1980s, Muslims have succeeded in influencing the making of government domestic policy for the interests of Islam and Muslims. For this reason, it is interesting to consider how Muslims' increasing pressure on the government affect the course of Indonesia's foreign policy, so far as Islamic issues are at stake. This paper attempts to delineate the "role", or more appropriately the position of Islam in Indonesia's foreign policy by taking into consideration several cases, involving Islam directly or indirectly.DOI: 10.15408/sdi.v7i3.701